Bridging the Gap Between Cultural Relativism and Universality of Human Rights: Indonesia Attitudes - Pratiwi, Cekli Setya (JILS (Journal of Indonesian Legal Studies), 2020)
Debates on the universality of human rights and cultural relativism seem to be eternal and will continue to exist as societal dynamics bring different views, concepts, and understandings of human rights and culture. However, it cannot be denied that modern international human rights law which is currently being referred to and adopted by the international community, still creates gaps in the protection of human rights. Meanwhile, the development of cultural relativism in the 20th century is quite successful in bridging the gap between the two and contributing positively to the implementation of international human rights law at the domestic level. Nonetheless, the cultural relativism approach presents critiques and challenges. By using various secondary resources, this paper begins with the concept of, debates between, and challenges of cultural relativism and universality of human rights. The paper indicates that the contribution of cultural relativism can be seen from building tolerance and protection of communal rights, the rights of marginal groups, and the optimization of domestic law when dealing with some competing’s rights. This is a good opportunity to reduce discriminatory actions against marginalized groups for maintaining tolerance and harmony in a plural society. The effectiveness of the application of "margin appreciation" in Europe should be the best practice to actualize "Asian values" or "African values" in formulating the concepts of "public morality" or "public order" clearly and precisely. The cultural relativism approach may not be used by a government to justify any human rights violation. Both of these are important considerations for Indonesia because of its ambiguous attitude in placing these two theories appropriately and purposefully.